Short term settlement of footing on snow foundation - Mahajan, Puneet (Defence Science Journal, 2002)
"A constitutive theory for snow, developed by the authors, is applied to solve for the short-term settlement of footing on snow foundation. The constitutive law used is a microstructurally-based formulation which includes the effects of bond deformation and fracture. It also includes transient creep effects and strain hardening of snow. The foundation problem is solved for stress and displacement distribution, with two different loads of 0.008 MPa and 0.1 MPa distributed uniformly over a part of the top face. The stress distribution matches closely with the existing theoretical results.